Photosynthetic nature of ice algae and their contribution to the primary production in lagoon Saroma Ko, Hokkaido, Japan - Satoh, Hiroo; Yamaguchi, Yukuya; Watanabe, Kentaro; Tanimura, Atsushi; Fukuchi, Mitsuo; Aruga, Yusho (National Institute of Polar Research, 1989)
P(論文) Photosynthetic activity of ice algae and phytoplankton was investigated under sea ice at two stations (ca. 44°10'N, 143°46'E) in lagoon Saroma Ko, Hokkaido, Japan, in early March 1987. Water temperature and salinity ranged from -1.1 to -1.4℃ and from 32.4 to 33.5, respectively. The maximum chlorophyll a concentrations of ice algae within 4cm from the bottom of sea ice and phytoplankton in water column were 385 and 0.77 mg m^<-3>, respectively. The maximum photosynthetic rate (1.12 mgO_2 mgchl, a^<-1> h^<-1>) of ice algae was obtained under 37.5 μEm^2 s^<-1>, which corresponds to only 3% of incident solar radiation. These results demonstrate the low-light adaptation of ice algae grown under low light conditions. The optimum temperature for photosynthesis of ice algae was around 8℃. In situ measurements on a clear day gave the primary production of 1.59 mgCm^<-2> h^<-1> by ice algae and that of 1.92 mgCm^<-2> h^<-1> by phytoplankton. It was concluded that the ice algae contribute to a considerable extent to the production of organic carbon in the ice-covered area of Saroma Ko during winter. departmental bulletin paper